Multifunctional and stretchable graphene/textile composite sensor for human motion monitoring. Issue 32 (18th June 2022) - Zhou, Yi; Myant, Connor; Stewart, Rebecca
Abstract: Sensors based on electronic textiles (e‐textiles) have become increasingly prominent in the field of biomechanical monitoring technology due to multiple properties such as being lightweight, flexible, and comfortable, with increasing potential in incorporating into long‐term monitoring devices. Previous research has been conducted into textile strain sensors based on graphene for human motion monitoring, however most graphene e‐textile strain sensors exhibit poor sensitivity and stretchability. To our knowledge, no previous research has looked at knitted graphene‐based fabrics in regards to the fabric composition of the substrate. In this paper, we propose a graphene/fabric composite sensor using a cost‐effective dip coating method of an acrylic/Spandex knit fabric, and further explores its mechanical, electrical, and sensing properties. The developed graphene/textile composite sensor has a wide sensing range (up to 344%) and exhibits a good sensitivity with a high gauge factor of up to 16. As a wearable sensor, our sensing fabric can detect both large and subtle human motions and is able to distinguish between various ranges of joint movements, demonstrating its ability to function as a human motion monitoring system. Our sensor further exhibits the ability to be used as a supercapacitor or capacitive pressure sensor. Abstract :